THE IMPACT OF PROTON PUMP INHIBITORS ON THE GUT MICROBIOME: A REVIEW - Katarzyna Jania,; Tomasz Antczak,; Monika Gajda-Bathelt,; Monika Dąbek,; Zuzanna Perlicka,; Karolina Smolińska,; Paulina Sadkowska,; Julia Kulczycka,; Weronika Popow,; Michał Ciołkosz, (International Journal of Innovative Technologies in Social Science, 2025)
Background: Proton pump inhibitors (PPIs) are among the most commonly prescribed medications for acid-related gastrointestinal disorders due to their high efficacy and favorable safety profile. However, emerging evidence suggests that their prolonged use may adversely affect the gut microbiome, potentially leading to clinically relevant complications.Aim: This review aims to analyze the impact of PPI therapy on the composition and function of the intestinal microbiota.Methods: A comprehensive literature review was conducted using databases such as PubMed and Google Scholar. Search terms included “proton pump inhibitors,” “gut microbiota,” “dysbiosis,” and related keywords. Articles were selected based on relevance and recent contributions to understanding PPI-induced microbial changes.Results: PPIs function by irreversibly inhibiting the H⁺/K⁺-ATPase enzyme in gastric parietal cells, thereby suppressing acid secretion. While beneficial in treating conditions like GERD, peptic ulcers, and Helicobacter pylori infection, PPIs also increase gastric pH, weakening the natural defense against ingested pathogens. This alteration facilitates the survival and migration of oral and exogenous microorganisms into the lower gastrointestinal tract, contributing to dysbiosis. Studies reveal significant shifts in microbial composition, including increased prevalence of Klebsiella pneumoniae, Fusobacterium nucleatum, and Campylobacter concisus. Clinically, such changes have been associated with a higher risk of small intestinal bacterial overgrowth (SIBO), Clostridioides difficile infection, and other enteric pathogens.Conclusion: While PPIs remain a cornerstone in gastrointestinal therapy, clinicians should be aware of their potential to disrupt gut microbiota. Rational prescribing practices, guided by appropriate indications and minimal effective duration, are essential to mitigate microbiota-related risks.